1971
DOI: 10.2514/3.6451
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic instabilities in a weakly ionized, radiating plasma

Abstract: A unified, linear theory is formulated for MHD waves at low magnetic Reynolds number, propagating transverse to the magnetic field in a weakly ionized, radiating plasma. The set of equations obtained from a two-fluid model yields a fifth-order dispersion relation whose roots correspond to four waves: magnetoacoustic (a paired wave), thermal, electrothermal, and "ionization-rate." To bring out the physics of each of these waves, simplifying assumptions are made, and "simple" analytical wave solutions are found.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 13 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…The shape and the rotation direction seem to be the same as with nonuniform structure that occurs at weak ionization of noble gas in seed-plasma scheme [17]. from dispersion equations that variation of plasma parameters occurs mostly without relative speed with respect to fluid [18]. Figure 5 shows the detailed distribution of electron temperature at 90 μs and θ = 0°.…”
Section: Relationships Between Generator's Inlet Total Temperature/rementioning
confidence: 72%
See 1 more Smart Citation
“…The shape and the rotation direction seem to be the same as with nonuniform structure that occurs at weak ionization of noble gas in seed-plasma scheme [17]. from dispersion equations that variation of plasma parameters occurs mostly without relative speed with respect to fluid [18]. Figure 5 shows the detailed distribution of electron temperature at 90 μs and θ = 0°.…”
Section: Relationships Between Generator's Inlet Total Temperature/rementioning
confidence: 72%
“…This is consistent with the conclusion drawn by Hougen and colleagues. from dispersion equations that variation of plasma parameters occurs mostly without relative speed with respect to fluid [18]. Here, there is one wave of ionization degree and two waves of electron temperature, and the one wave of ionization degree propagates between the two waves of electron temperature.…”
Section: Relationships Between Generator's Inlet Total Temperature/rementioning
confidence: 99%
“…Local steady-state analysis taking the linear theory of ionization instability into account 3-6 ͓Figs. [11][12][13] In comparison with the case of previous larger-scale MHD generators using lower-density magnetic flux, 14-18 the control of the plasma state is more vital for the compact MHD generator owing to the narrow plasma stable region under high-density magnetic flux. However, a nonequilibrium plasma will be conditionally unstable if the Hall parameter exceeds its critical value.…”
mentioning
confidence: 99%
“…Research on nonequilibrium MHD generators using linear perturbation analysis has confirmed that four types of waves exist in the plasma and electric fluid inside a generator: an electrothermal wave, an ionization-rate wave, a magneto-acoustic wave, and a thermal wave [1]. The electrothermal (E.T.)…”
Section: Introductionmentioning
confidence: 99%